New proposal involving nanoformulated melatonin targeted to the mitochondria as a potential COVID-19 treatment - Martín Giménez, Virna Margarita (2020)
Melatonin may be a powerful auxiliary therapy in the prevention and treatment of viral infections, such as coronavirus disease 2019 (COVID-19). Casually, the so-called ‘super immunity’ of bats and the usually high levels of melatonin in children could contribute to their high resistance to the SARS-CoV-2 virus. Melatonin seems to play a key role in suppressing COVID-19 infections. This endogenous antioxidant inhibits cell apoptosis, blocks the inflammasomes that mediate lung inflammation, reduces blood vessel permeability which limits alveolar edema, improves anxiety and sleeps habits that stimulate general immunity and prevents lung fibrosis. These complications, which are usually the main consequences of COVID-19, may be significantly attenuated by melatonin...